2018
DOI: 10.33607/bjshs.v4i83.313
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Muscular Performance Indices during the 30‑s Vertical Jump Test in Endurance and Sprint Cohorts

Abstract: Research background and hypothesis. According the methodological requirement testing procedures do not modify the main training objectives. It is well known that specificity of performance assessment tests is important if we want to compare performance of different groups tested.Research aim was to find out the peculiarities of muscular performance indices in sprint and endurance cohorts while performing a 30-s vertical jump test.Research methods. The participants of the study were two groups of athletes, i. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This is in agreement with previous research as decreases in JH and flight time have consistently been reported with fatigue. [4][5][6] It is interesting that Pupo and colleagues noted larger decreases in JH, after the 30s continuous jump test (26% versus 17.4% in the current study). This raises the question of if the load's relative intensity is associated with the fatigue magnitude to be simulated.…”
Section: Previous Research Has Indicated Decreases In Maximal Hip Andsupporting
confidence: 40%
See 2 more Smart Citations
“…This is in agreement with previous research as decreases in JH and flight time have consistently been reported with fatigue. [4][5][6] It is interesting that Pupo and colleagues noted larger decreases in JH, after the 30s continuous jump test (26% versus 17.4% in the current study). This raises the question of if the load's relative intensity is associated with the fatigue magnitude to be simulated.…”
Section: Previous Research Has Indicated Decreases In Maximal Hip Andsupporting
confidence: 40%
“…Fatigue may be accompanied by decreases in jump height, flight time, eccentric force production, power, vertical stiffness, and knee flexion angles. [4][5][6] Fatigue has also been associated with increases in ground contact time and with decreases in angular velocities and accelerations in jumps. 4,[6][7] Furthermore, fatigue has been associated with knee joint stability decreases, that may increase the risk of injury in both males and females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation